Identification and Antifungal Susceptibility Analysis of Stephanoascus ciferrii Complex Species Isolated From Patients With Chronic Suppurative Otitis Media - Guo, Penghao; Wu, Zhongwen; Liu, Pingjuan; Chen, Yili; Liao, Kang; Peng, Yaqin; He, Yuting (Frontiers in Microbiology, 2021)
Background Stephanoascus ciferrii is a heterothallic ascomycetous yeast-like fungus. Recently, the concept of S. ciferrii complex has been proposed and it consists of S. ciferrii, Candida allociferrii, and Candida mucifera. We aimed to identify 32 strains of S. ciferrii complex isolated from patients with chronic suppurative otitis media (CSOM) at the species level and analyze the morphology and antifungal susceptibility profiles of the three species. Method The sequencing of the internal transcribed spacer (ITS) region and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) were used to identify S. ciferrii complex species. The SARAMIS software was used for cluster analysis of the mass spectra. All the strains were cultured on Sabouraud dextrose agar (SDA) and CHROM plates for 7 days. In the meantime, colonies of the 32 strains went through Gram staining. The Sensititre YeastOne YO10 colorimetric panel was used for the antifungal susceptibility analysis. Results There were 10 strains of C. allociferrii (31.25%), six strains of C. mucifera (18.75%), and 16 strains of S. ciferrii (50%) in the 32 strains of S. ciferrii complex according to the sequencing of the ITS region. MALDI-TOF MS could identify S. ciferrii but showed no results for C. allociferrii and C. mucifera. The cluster analysis of the mass spectra by SARAMIS indicated that the MALDI-TOF MS could distinguish the three species. The morphology characteristics of the three species were similar. As for antifungal susceptibility, S. ciferrii and C. mucifera tended to have high fluconazole MICs compared with C. allociferrii. C. mucifera and C. allociferrii had relatively low flucytosine MICs while S. ciferrii owned high flucytosine MICs. Besides, C. mucifera tended to have a higher MIC value than S. ciferrii for amphotericin B and C. allociferrii for anidulafungin, micafungin, and caspofungin. Conclusion The antifungal susceptibility profiles of the three species of S. ciferrii complex had their own characteristics. Besides, more mass spectra of C. allociferrii and C. mucifera are needed to construct the reference database for S. ciferrii complex species, enabling MALDI-TOF MS to identify S. ciferrii complex at species level.